Ductile failure prediction of pipe-ring notched AISI 316L using uncoupled ductile failure criteria. (June 2021) - Bianchetti, C.; Muñoz, D. Pino; Leblé, B.; Bouchard, P.-O.
Abstract: The goal of this work is to predict ductile failure of pipe-ring notched AISI 316L specimens, where notches mimic the geometry of corrosion defects. Uncoupled damage models are used to that end. The Johnson-Cook and Lou-Huh criteria are calibrated. The uncoupled damage models are calibrated using experimental results from testing pipe-ring notched specimens. Calibration was achieved using a hybrid experimental-numerical approach. Six notch shapes are studied. Experimental matrices are designed to determine these shapes, and the pipe-ring notched specimen is inspired from the literature. Calibration of the uncoupled damage models require a ductile crack initiation indicator. The first indicator was based on the derivative curves of the force versus the connectors displacement curve. The second was based on the raw images of the gage section. The third was based on a percentage of the connectors displacement at fracture. Results show that ductile fracture depends on the Lode paramater. As a consequence, the Lou-Huh criterion is more effective at predicting ductile fracture than the Johnson-Cook criterion. Highlights: Notched samples were designed to mimic the corrosion defects observed on 316L pipes. A methodology was developed to cover η and L locally underwent by pressurized pipes. Ductile fracture models were calibrated using a hybrid approach. The experimental crack initiation indicator reliability requires further improvement. A slight Lode parameter influence was observed at high η.